Proposed new interior design for Kaw Kaw Burger Bakar Cafe for Kaw Kaw Burger Bakar Sdn Bhd at Lot 2/28 Festival Walk,Perak Tourism Hub.Medan Ipoh Bestari,Ipoh Perak / Wan Sobri Wan Harun - Wan Harun, Wan Sobri (Faculty of Architecture, Planning and Surveying, 2012)
Final project report is something very important in the diploma level.This is the manifestation of an individual knowledge about all aspect of the process that has been learning from the basic to the higher level.This is because in order to ensure students can carry out interesting presentation in interior design. This final report is about to proposed new interior design scheme of kaw kaw burger bakar cafe for kaw kaw burger bakar sdn bhd. At lot 2/28 festival walk,perak tourism hub.medan ipoh bestari.ipoh perak.the aim of this project for proposed a new image to it interior.design space more organized and give individual affect the space.To created a new design scheme of space requrement for the cafe. To complete the requrement of this project .interview,research and observation is being doing to make sure the data are required and will be analyzed in the design process.Thus.the requirements are depend on the location that has to be strategic,size,image,circulation and the character of the cafe.so the customers will feels more relax,friendly atmosphere,cleanliness,comfort,and convenience.